Calcium/Copper Alginate Framework Doped with CuO Nanoparticles as a Novel Adsorbent for Micro-extraction of Benzodiazepines from Human Serum - Rahbar, Nadereh; Ahmadi, Fatemeh; Ramezani, Zahra; Nourani, Masoumeh (Current Pharmaceutical Analysis, 2021)
Background: Sample preparation is one of the most challenging phases in pharmaceutical analysis, especially in biological matrices, affecting the whole analytical methodology. Objective: In this study, a new Ca(II)/Cu(II)/alginate/CuO Nanoparticles Hydrogel Fiber (CCACHF) was synthesized through a simple, green procedure and applied for fiber micro solid-phase extraction (FMSPE) of diazepam (DIZ) and oxazepam (OXZ) as model drugs prior to high-performance liquid chromatography-UV detection (HPLC-UV). Methods: Composition and morphology of the prepared fiber were characterized and the effect of main parameters on the fiber fabrication and extraction efficiency have been studied and optimized. Results: In optimal conditions, calibration curves were linear, ranging between 0.1–500 μg L−1 with regression coefficients of 0.9938 and 0.9968. Limit of Detection (LOD) (S/N=3) and Limit of Quantification (LOQ) (S/N=10) of the technique for DIZ and OXZ were 0.03 to 0.1 μg L−1. Within-day and between-day Relative Standard Deviations (RSDs) for DIZ and OXZ were 6.0–12.5% and 3.3–9.4%, respectively. Conclusion: The fabricated adsorbent has been substantially employed to the extraction of selected benzo-diazepines (BZDs) from human serum real specimens and the obtained recoveries were also satisfactory (82.1-109.7%).
Keywords: hydrogel